2007
DOI: 10.1037/1053-0797.17.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Emotions before, during, and after dreaming sleep.

Abstract: The aim of this study was to provide a preliminary overview of the emotions before, during, and after dreaming sleep in Chinese people. One hundred Chinese participants were included in the study. Cheerful emotions, including interest, exhilaration, and enjoyment, were pervasive in the collected dreams, although anxiety was also a common type of emotion. Positive correlations were found between the intensities of dream, presleep, and postsleep emotions. Significant reductions in intensity were noted in the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
48
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 53 publications
11
48
3
Order By: Relevance
“…Given that SWB largely reflects positive mood, this finding is in keeping with other research showing that people who reported more frequent nightmares also reported negative effects on daytime mood such as anxiety, depression, and stress (Blagrove et al, 2004;Cummins et al, 2012;Schredl, 2009;Yu, 2007). As expected, those who reported having nightmares had reduced SWB compared with participants who reported experiencing no bad dreams or nightmares.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Given that SWB largely reflects positive mood, this finding is in keeping with other research showing that people who reported more frequent nightmares also reported negative effects on daytime mood such as anxiety, depression, and stress (Blagrove et al, 2004;Cummins et al, 2012;Schredl, 2009;Yu, 2007). As expected, those who reported having nightmares had reduced SWB compared with participants who reported experiencing no bad dreams or nightmares.…”
Section: Discussionsupporting
confidence: 83%
“…As expected, those who reported having nightmares had reduced SWB compared with participants who reported experiencing no bad dreams or nightmares. Given that SWB largely reflects positive mood, this finding is in keeping with other research showing that people who reported more frequent nightmares also reported negative effects on daytime mood such as anxiety, depression, and stress (Blagrove et al, 2004;Cummins et al, 2012;Schredl, 2009;Yu, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ameka (2002) asserts that these bodily referents in everyday emotion terms are good evidence of cultural scripts linking the body with emotions, including which particular parts of the body are scripted with which particular emotions. Yu (2007) describes how Chinese language conceptualizes the heart as the seat of emotions. This is perhaps not surprising, knowing that the Chinese ideograph for "love" includes the ideograph for "heart" (Tung 1994).…”
mentioning
confidence: 99%
“…As with sleep problems, dreaming is sensitive to affect valence and emotional concerns experienced during wakefulness (Gilchrist, Davidson, & Shakespeare-Finch, 2007;Malinowski, Fylan, & Horton, 2014;Schredl & Reinhard, 2009;Yu, 2007aYu, , 2015. According to Yu (2013bYu ( , 2013c, dream experiences are facilitated by both pleasant and unpleasant emotions -such as anxiety and anger -and suppressed by superego functions, including conscientiousness, agreeableness, and repressive defensiveness.…”
Section: Introductionmentioning
confidence: 99%